Informatization of education and person - oriented principle: how to teach everyone in a similar way but differently - Korol, Andrey D. (Pedagogika, 2014)
The contents of the given article reveals pedagogical basics of dialogization of student’s education due to informational educational technologies, development of heuristics student’s skills to realize the personal approach in education. The person-oriented sense of telecommunications in the educational process is the opportunity for the pupil to create “one’s own” in the dialogue with “other people’s”, to develop an individual educational path.